الفضاء السردي في الرواية الصوفية المعاصرة - حراث, أسماء (كلية الأدب العربي والفنون, 2025)
تتناول هذه الدراسة موضوع الفضاء السردي في الرواية الصوفية المعاصرة، بوصفه عنصرا بنائيا يساهم في إنتاج المعنى وتكثيف التجربة الروحية داخل النص الأدبي. وقد تم اختيار رواية قواعد العشق الاربعون " لإليف شافاق كنموذج تطبيقي ، لما تحمله من تمثيلات صوفية عميقة تتقاطع فيها الأزمنة والأمكنة والأصوات السردية. ترتكز الدراسة على تحليل ثلاثة أنماط من الفضاءات الفضاء النصي، الزمني ، والمكاني ، وكيفية تفاعلها في تشكيل بنية سردية ذات بعد تأملي وروحي ، وتسعى إلى إبراز دور هذه الفضاءات في تجسيد المفاهيم الصوفية وتوسيع أفق التلقي، من خلال المزج بين السرد الواقعي والتجربة العرفانية. This study addresses the topic of narrative space in contemporary surf novels, considering it as a structural lament that contributes to the production of meaning and the shaping of the spiritual experiences within the literary text. The novel the forty rules of love by Elif shafak was selected as an model due to its deep sufi representations, where times, places, and voices intersect in a complex narrative fabric. The study focuses on analyzing three types of spaces textual space, temporal space, and spatial space, and how they interact in forming a narrative structure Characterized by contemplation and spirituality, it seeks to highlight the robe of these spaces in emboldening Sufi concepts and bro dining the horizon of reception by blending realistic narrative with experiential and mystical dimensions
قواعد العشق الاربعون أنموذجا
Keywords: الفضاء الروائي ، الصوفية، السرد ، الزمان ، المكان; Narrative space, Sufism, Narrative, Temporality spatiality